1997
DOI: 10.1016/s0895-7061(97)00323-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Angiotensin Converting Enzyme Gene Polymorphism or Serum Enzyme Activity With Coronary Artery Disease in Japanese Subjects

Abstract: The association of an insertion/deletion (I/D) polymorphism in the angiotensin converting enzyme (ACE) gene or the serum activity of ACE with coronary artery disease (CAD) was investigated in Japanese men and women. The ACE genotype of 947 CAD subjects who underwent coronary angiography and of 893 control subjects was determined by polymerase chain reaction analysis. No association of the DD genotype or the D allele with CAD was observed in men or women. In a low risk group (defined by a body mass index below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In two large studies from Copenhagen, a case-referent study (n = 10,150) and a retrospective cohort study (n = 7263), there was no evidence of an association of the ACE I/D gene polymorphism and myocardial infarction or ischemic heart disease in either males or females (Agerholm-Larsen et al, 1997). In a Japanese study of coronary artery disease in subjects who underwent coronary angiography (n = 947), there was no association between ACE genotype or serum ACE activity and disease (Fujimura et al, 1997). Arnett et al (1998) found no evidence that the ACE I/D polymorphism was associated with carotid intima-media thickness in a sample of middle-aged adults with no history of coronary artery disease (n = 495).…”
Section: Angiotensin-converting Enzyme Insertion/ Deletion Polymentioning
confidence: 98%
“…In two large studies from Copenhagen, a case-referent study (n = 10,150) and a retrospective cohort study (n = 7263), there was no evidence of an association of the ACE I/D gene polymorphism and myocardial infarction or ischemic heart disease in either males or females (Agerholm-Larsen et al, 1997). In a Japanese study of coronary artery disease in subjects who underwent coronary angiography (n = 947), there was no association between ACE genotype or serum ACE activity and disease (Fujimura et al, 1997). Arnett et al (1998) found no evidence that the ACE I/D polymorphism was associated with carotid intima-media thickness in a sample of middle-aged adults with no history of coronary artery disease (n = 495).…”
Section: Angiotensin-converting Enzyme Insertion/ Deletion Polymentioning
confidence: 98%
“…The ACE Ins/Del polymorphism has been correlated with variations in ACE activity and blood pressure, and risks for myocardial infarction and other cardiovascular disorders (10,11,(38)(39)(40). However, other studies have failed to demonstrate such associations in different populations (14)(15)(16)41). These discrepant results may be related to the different ethnic origins of the studied groups.…”
Section: Discussionmentioning
confidence: 99%
“…32 A previously meta-analysis of 15 studies (data from 3394 patients with myocardial infarction and 5479 32 in 1994. In contrast with all these results, Fujimura et al 34 concluded that the ACE I/D polymorphism is not an important determinant of CAD. Several reasons may account for the positive association in our study compared with some previous data concerning the negative association of ACE gene polymorphism with CAD.…”
Section: Discussionmentioning
confidence: 83%